Conceptual Design And Dynamical Analysis Of Aerostat System - Mahmood, Khurrum (2020)
Tethered aerostats are an efficient aerial system to be used for different applications. Tactical category of tethered aerostat systems is deemed as an emergency respondent system in restoration of communication aftermath a natural disaster. They operate without a propulsive and control system making it easy to deploy. However, it has to remain stable in the presence of atmospheric winds and minimize the drift due to wind called blow-by. This research thesis presents a novel streamlined aerostat configuration to be used as a tactical system in which the hull fineness ratio and fins are designed to generate aerodynamic lift to minimize the blow-by. The optimized design obtained using this approach can operate with lesser static lift that reduces the aerostat size making it cost effective and compact.The aerostat design approach that includes aerostatics, mass estimation, aerodynamics, static stability and blow-by is used to develop a design algorithm in MATLAB®. The design and optimization of the aerostat is carried out by taking payload mass of 10 kg and operating altitude to be 300 meter. The baseline configuration for the desired mission has been obtained using a design algorithm. The statistical values of the selected design variables that include hull fineness ratio, fin area and fin position of the existing aerostat are used to obtain the baseline configuration. The sensitivity analysis has been carried out to determine the effect of design variables on the aerostat mass and blow-by. The aerostat is optimized by setting minimization of mass as the objective function, taking lower and upper bounds of the design variables and blow-by limit as the constraint. The results show that the optimized configuration has a smaller hull volume that reduces the mass of the system. The fins of the optimized aerostat generate aerodynamic lift to operate within the blow-by limits along with providing rotational stability. The optimized configuration of the aerostat shows a reduction in volume to 120 m3 from 170 m3, reduction in mass to 71.6 kg from 90.65 kg. The reduction in volume of optimized configuration reduces the LTA gas Helium cost up to USD1925 (RM7700). A graphic user interface has been developed using MATLAB® app developer for design application. The design code is linked with the graphic user interface of the design app in which the payload mass, operating altitude and material properties are the input parameters. The geometric, mass and performance parameters for the conceptual design are obtained from the design app. The dynamical analysis of the aerostat is conducted by developing a three degree of freedom simulation model. Simscape MultibodyTM, an extension of MATLAB®/Simulink that employs a block-based modelling technique is used to develop the three degrees of freedom model. The aerostat is modeled as a single rigid body while the tether has been modeled as a sequence of elements connected at nodes through a revolute degree of freedom. The aerostat is simulated for varying winds, gusts and turbulent wind to analyze the longitudinal stability. The results show that the optimized aerostat configuration has longitudinal dynamic stability for the different wind scenarios. The aerostat attains steady state after encountering a varying wind or gust wind within 40 secs with ±3o fluctuations in pitch. For high intensity turbulent wind, the aerostat fluctuates with ±1.2 m/s horizontal velocity, ±0.2 m/s vertical velocity and ±3.5o pitch.